Healthy Living Practices and Housing Quality as Risk Factors for Tuberculosis in Toddlers - Lenie Marlinae; Agung Waskito; Laily Khairiyati; Ani Kipatul Hidayah; Anugrah Nur Rahmat; Husaini Husaini; Syamsul Arifin; Agung Biworo; Muhammad Rasyid Ridha; Anis Kamila Saleha (Jurnal Berkala Kesehatan, 2025)
Tuberculosis in young children is influenced by environmental conditions and household hygiene practices, as this age group has an underdeveloped immune system. This study aims to examine the association between housing conditions—such as lighting, ventilation, and housing density—and hygiene practices and healthy lifestyles with the incidence of tuberculosis in toddlers. A case-control study was conducted involving 42 participants (21 cases and 21 controls) in the service area of the Martapura 2 Community Health Center. Data were collected through home observations, interviews with parents, and direct measurements, and analyzed using chi-square or Fisher’s exact tests and logistic regression. The results showed that poor hygiene and healthy lifestyle practices (p = 0.026; OR = 5.667) and inadequate lighting (p = 0.045; OR = 5.455) were significantly associated with tuberculosis incidence among toddlers. Multivariate analysis identified hygiene and healthy living practices as the most dominant factor (p = 0.031; Exp(B) = 4.978), while lighting showed a near-significant association (p = 0.055; Exp(B) = 4.692). Housing density and ventilation were not significantly associated with tuberculosis incidence. These findings highlight the importance of improving household hygiene practices and ensuring adequate lighting as key strategies to reduce the risk of tuberculosis in toddlers.